2001
DOI: 10.1007/s11934-001-0040-x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction and depression: Etiology, prevalence, and treatment

Abstract: Sexual dysfunction and depression are very common conditions that are age-related and chronic. In men, epidemiologic studies have confirmed a strong correlation between erectile dysfunction and symptoms of depression. Both conditions have a significant negative impact on the quality of life of patients and their partners. Several studies showed that restoration of normal sexual function improves the quality of life of patients and their partners, regardless of treatment method. The literature review and recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 43 publications
0
25
1
2
Order By: Relevance
“…As already known, depressive symptoms cause both SD and worsening in quality of life in the general population (43,44). In our study, the differences between the patient and control groups reported in all the three fields had been re-examined by covariance analysis by controlling the depression scores.…”
Section: Discussionmentioning
confidence: 89%
“…As already known, depressive symptoms cause both SD and worsening in quality of life in the general population (43,44). In our study, the differences between the patient and control groups reported in all the three fields had been re-examined by covariance analysis by controlling the depression scores.…”
Section: Discussionmentioning
confidence: 89%
“…It contains 36 items that calculate 8 dimensions including, physical functioning, physical cle mass, body composition, mood status and cognition. Overall, the restoration of the above parameters is expected to improve the quality of life [7][8][9]. However, few studies so far have reported positive effects of TRT on psychological well-being and quality of life [10,11].…”
Section: Short Form-36 (Sf-36)mentioning
confidence: 99%
“…Several studies showed sexual function improves the QoL in both men and their partners following treatment Shabsigh et al, 2001). It has been shown that the mood, overall sexual function, satisfaction in relationships and their overall QoL improves after treatment of ED .…”
Section: Quality Of Life Following Treatment Of Edmentioning
confidence: 99%